Some Aspects of Biology of Chola Punti Puntius Chola (Hamilton) from the Kangsa River (Bangladesh Journal of Scientific and Industrial Research, 2011)
The mean values of total length (75.89 ± 13.09 mm), standard length (54.98 ± 7.07 mm), fork length (60.86 ± 9.14 mm), head length (14.75 ± 2.05 mm), snout length (3.79 ± 0.61 mm), pre-dorsal length (31.53 ± 3.18 mm), height of body (20.2 ± 4.11 mm) and total weight (6.62 ± 3.55g) of combined sex of Puntius chola were calculated. Relationships between total length and standard length, fork length, head length, snout length and pre-dorsal length of Puntius chola were found to be linear, positive and highly significant. The length-weight relationship in male, female and combined sex were determined as Log W=-4.510+2.810 Log L, LogW=-4.204+2.685 Log L and Log W=4.465+2.808 Log L respectively. The mean values of condition factor from observed value (ko) of male, female and combined sex were determined as 1.36 ± 0.089, 1.599 ± 0.181 and 1.515 ± 0.192 respectively. The mean values of condition factor from calculated value (kc) of male, female and combined sex were found to be 1.362 ± 0.054, 1.6 ± 0.124 and 1.511 ± 0.075 respectively. The mean values of relative condition factor of male, female and combined sex were registered as 0.999 ± 0.044 , 0.999 ± 0.064 and 0.999 ± 0.112 respectively. Sex ratio was found to be 1:1. Key words: Standard length; Pre-dorsal length; Puntius chola; Morphomertric; Fish culture. DOI: 10.3329/bjsir.v45i4.7327 Bangladesh J. Sci. Ind. Res. 45(4), 309-314, 2010